Projetos para o desenvolvimento brasileiro no nordeste : Celso Furtado, Lina Bo Bardi, a ARTENE e a Escola de Desenho Industrial e Artesanto do MAM-BA, 1958 - 1964 - Souza, André Felipe Batistella (2016)
The industrialization took place in Brazil as a delayed event if compared to other countries that followed the industrial revolution. Here, this process happened based on the import substitution model, which was boosted by 1929 economic crisis. Juscelino Kubistchek and João Goulart hold Brazil's presidency in 1956, whose government launched the Goals Plan, which slogan was "fifty years in five". Besides the construction of Brasília, another project of great importance was the Superintendência de Desenvolvimento do Nordeste (SUDENE), an autarchy that aimed integrated actions implementation in order to enable social and economic transformations in the northeast territory. Ahead of SUDENE, founded in 1959, was the Paraiban economist Celso Furtado. At that time, the Italian-Brazilian architect Lina Bo Bardi moves to Bahia invited by Diógenes Rebouças in order to teach at the Federal University of Bahia. Bahia presented an opportunity for the elaboration of a cultural modernization project, with SUDENE support, through Furtado. In that context, Lina is invited by Juracy Magalhães to manage Bahia Museum of Modern Art, located at the architectonic complex of Unhão Solar, whose restoration project was of her own. In addition to the museum, were expected to run on Unhão the Museum of Popular Art, Center for Craft Study and Work and the School of Industrial Design and Crafts. Lina focused part of her activities in Northeast researching the northeastern's pre-craft. Craft in Northeast was encouraged by SUDENE's actions through ARTENE, a joint enterprise whose goals were to promote the increasing income of the craftsmen with technical training among other targets. This study revisits Lina Bo Bardi and Celso Furtado's experience in Bahia, highlighting matters such as political, economic and cultural as well as the importance of SUDENE and ARTENE. It was possible to identify the importance of the activities of Celso Furtado and Lina Bo Bardi in the Northeast between 1958 and 1964, for a proposal of Brazilian development, especially in what concerns to the industrialization and culture, from the questions related to the craftsmanship, to the formation of labor and the teaching of an industrial design linked to the cultural bases of the country.